X-ray source with variable photons energy for medicine applications - Shatokhin, R.A.; Vnukov, I.E.; Zhandarmov, Yu.V. (Вопросы атомной науки и техники, 2009)
The prospect of creation of the X-ray source with tunable wavelength on the base of a middle energy accelerator and mosaic crystals are analyzed. It is proved, that due to the contribution of diffracted bremsstrahlung, the mosaic crystals provide the essentially greater yield of hard radiation (w ≥ 20 keV), than perfect crystals. It is shown, that using a traditional scheme with one crystal for X-ray generation isn't acceptable for medicine applications. Double-crystal scheme is offered and analyzed, in which one crystal is located on the electrons beam, and another is used for monochromatization and parallel moving of the X-ray beam. It provides suppression of background bremsstrahlung, and there is no need to move the object when change the photons energy. Проведено аналіз перспективи створення джерела рентгенівського випромінювання зі змінюваною єнергією на основі електронного прискорювача середніх енергій та мозаїчних кристалів. Доведено, що мозаїчні кристали забезпечують більший вихід жорсткого випромінювання, порівнянно з ідеальними. Показано, що схема генерації випромінювання з одним кристалом неприйнятна із-за фону гальмового випромінювання. Запропонована та проаналізована схема з двома кристалами, де один розміщений під пучком електронів, а другий використовується для монохроматизації та паралельного переносу, чим забезпечується зменшення фону та відсутність необхідності переміщення об'єкта опромінювання при зміні енергії фотонів. Анализируются перспективы создания источника рентгеновского излучения с перестраиваемой энергией на основе электронного ускорителя средних энергий и мозаичных кристаллов. Доказано, что мозаичные кристаллы обеспечивают больший выход жёсткого излучения, чем совершенные. Показано, что однокристальная схема генерации излучения не применима для использования в медицине из-за фона тормозного излучения. Предложена и анализируется двухкристальная схема, где один из кристаллов установлен на пучке электронов, а другой используется для монохроматизации излучения и параллельного переноса, что обеспечивает подавление фона и отсутствие необходимости перемещения объекта облучения при изменении энергии фотонов.